Does Retention of Fibula in Transfibular Approach Leads to Complication?. Issue 4 (16th October 2019) - Abyar, Eildar; Hess, Matthew; McKissack, Haley; Johnson, Michael
Category: Ankle, Ankle Arthritis, Hindfoot Introduction/Purpose: A variety of operative approaches and fixation techniques have been described for tibiotalar (TT) and tibiotalocalcaneal (TTC) arthrodesis. In the past two decades, authors have begun to more robustly examine outcomes of the transfibular approach for TT arthrodesis and expanded its indication to include TTC fusion. The transfibular technique is broadly divided into two categories: 1) Complete excision of fibula 2) Soft tissue preservation techniques with retention of fibula. The purpose of this study was to retrospectively assess the surgery outcomes in transfibular approach and compare the fibula excision versus fibula retention techniques and examine the factors that play into the risk. Methods: Following institutional review board approval, a retrospective review was performed on all patients who underwent TT and TTC arthrodesis through a lateral transfibular approach with minimum 1 year clinical and radiologic follow up. All other operative approach and fixation combinations for arthrodesis were excluded. Primary outcomes examined were union rate, revisions, and complications related to fibula excision versus retention group. Sixteen patients underwent TT and TTC arthrodesis with fibular retention and twelve with fibular excision techniques. Results: The overall union rate was 89%, 87% (14 of 16 ankles) for the fibula retention group, and 91% (11 of 12) for fibula excision group (P = .72). Symptomatic nonunion requiring revision arthrodesis occurred in 6% (1 of 16) of the retention group versus 8% (1 of 12) in the excision group (P = .83). There were no significant differences in individual tibiotalar or subtalar union, reoperation, superficial wound problems, infection and symptomatic hardware rates. Elective hardware removal was performed in 12%(2of 16) in fibular retention group versus 25%(3 of 12) in fibula excision group (P = .39), none of the hardware removal was related to the fibula fixation. Each group had three episodes of reoperation due to non-union, osteomyelitis and painful hardware. Conclusion: Union, reoperation rates were similar in fibula resection versus retention groups. The frequency of infection and wound complication was not significantly different in both groups, despite the wide variety of patient population and preoperative indications.